A construção da denúncia: o caso dos fiscais do ISS em São Paulo e as práticas processuais de repressão à corrupção - Prado, Arthur Sodré (2017)
This work examines the Prosecutorial discretion in corruption cases through a case study. Using a qualitative approach, I have observed a group of criminal procedures since their common beginning until the Judge’s appraisal of several indictments of São Paulo’s city hall public agents, their family members and colleagues accused for public extortion, conspiracy and money laundering (called by me as 'The ISS agents case'). The idea was to understand how the Public Prosecutors, in the Brazilian practice, chooses the investigation targets and selects individuals to be considered liable for corruption events. I observed the results under three main theoretical models frequently used to explain the Prosecutorial discretion: The mandatory model, the opportunity model and a model in their middle, the legally bounded opportunity model. I also have adopted a cross-cut view to see how the differences between public extortion and bribery are considered in both criminal and criminal procedure angles. The conclusion was that the ISS agents case shows a trend to enlarge the prosecutorial discretion with no clear indicia of how to control their choices. The prosecutors work in an institutional multiplicity environment; they choose corruption crimes to investigate 'following the money'. The need of evidences of the quid pro quos and about new facts, however, stimulates the Prosecutors to settle with suspects. In the ISS agents case, the use of an unclear distinction between bribery and public extortion reveals a way to bypass the Brazilian criminal plea agreement statutes by the exchange of immunity to the companies for evidences of bribe payments and data about new facts. This trend is not necessarily sign of an evolution. Brazil is dealing with a dilemma: Massive corruption scandals are being revealed, but the civil rights can be affected and seriously harmed by the guidance of the criminal procedure just for the increase of the social control without considering the respect for the due process clauses and the right for a fair trial.